Biomedical data management and graph online querying : VLDB 2015 Workshops, Big-O(Q) and DMAH, Waikoloa, HI, USA, August 31-September 4, 2015, Revised selected papers /: VLDB 2015 Workshops, Big-O(Q) and DMAH, Waikoloa, HI, USA, August 31-September 4, 2015, Revised selected papers. (2016) - Unknown
No abstract available